Seismic response control of frame structures using magnetorheological - Xu, Y. L. (Earthquake engineering & structural dynamics.)
Semi-active control of buildings and structures for earthquake hazard mitigation represents a relatively new research area. Two optimal displacement control strategies for semi-active control of seismic respones of frame structures using magnetorheological (MR) dampers or electrorheological (ER) dampers are proposed in this study. The efficacy of these displacement control strategies is compared with the optimal force control strategy. The stiffness of brace system supporting the smart damper is also taken into consideration. An extensive parameter study is carried out to find the optimal parameters of MR or ER fluids, by which the maximum reduction of seismic response may be achieved, and to assess the effects of earthquake intensity and brace stiffness on damper performance. The work on example buildings showed that the installation of the smart dampers with proper parameters and proper control strategy could significantly reduce seismic responses of structures, and the performance of the smart damper is better tha that of the common brace or the passive devices. The optimal parameters of the damper and the proper control strategy could be identified through a parameter study.